2014
DOI: 10.1603/en13234
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Resistance by Silicon in Wheat Plants to Alate and Apterous Morphs ofSitobion avenae(Hemiptera: Aphididae)

Abstract: Despite the knowledge about the effects of silicon augmenting antibiosis and nonpreference of plants by apterous aphids, few studies exist on such effects with alate aphids. This study evaluated the effects of silicon fertilization on the biology of alate and apterous morphs of Sitobion avenae (F.) (Hemiptera: Aphididae), and the effect on nonpreference by S. avenae alates for wheat plants with or without silicon fertilization. A method for rearing aphids on detached leaves was evaluated comparing the biology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 31 publications
4
41
0
10
Order By: Relevance
“…Mortality on egg (90-100%) Gamma irradiation (200 Gy) [45] essential nutritional element to the plants [49], but as potassium silicate, calcium silicate, and sodium silicate from other sources has determined the tolerance of many plant species to insects [50][51][52][53]. Silicon promoted cuticle thickening and accumulation of crystals on the leaf stomata in sugarcane [54].…”
Section: Activity On Insect Stage Treatment (Concentration or Dose) [mentioning
confidence: 99%
“…Mortality on egg (90-100%) Gamma irradiation (200 Gy) [45] essential nutritional element to the plants [49], but as potassium silicate, calcium silicate, and sodium silicate from other sources has determined the tolerance of many plant species to insects [50][51][52][53]. Silicon promoted cuticle thickening and accumulation of crystals on the leaf stomata in sugarcane [54].…”
Section: Activity On Insect Stage Treatment (Concentration or Dose) [mentioning
confidence: 99%
“…A signifi cant reduction of the number of aphids was observed during aphids' colonization as a result of Si application. More recently, Si fertilization was reported to induce resistance of wheat plants to apterous morphs via antibiosis as shown by reduced fecundity, reproductive period, longevity, intrinsic rate of increase and net reproductive rate; however, alates were unaffected (Dias et al 2014 ). Plants treated with Si had fewer alate aphids in both the vegetative and reproductive phases compared with Si-untreated plants.…”
Section: Nutritional Defencesmentioning
confidence: 99%
“…In wheat, it was found that Si decreased the incidence and severity of diseases (Bélanger et al, 2003;Guével et al, 2007) and increased the resistance to pests (Dias et al, 2014), to salinity (Tuna et al, 2008), and to water deficit (Gong et al, 2005).…”
Section: Introductionmentioning
confidence: 99%